Utility of Immunohistochemistry in the Subtyping of Lung Carcinoma on Small Biopsies (Pulse, 2024)
Background: Hamstring tendon auto grafts in the form of quadrupled Background and objectives: In the era of precision medicine, the important task of today’s pathologist is to classify lung carcinoma into specific histologic subtypes. Thus enables the scope to identify the molecular target for targeted therapy. Hematoxylin and eosin stain alone cannot subtype lung carcinoma when particularly it exhibits solid pattern of growth. This challenge becomes more pronounced when working with small biopsy samples.Methodology and result: A retrospective cross-sectional study was conducted to evaluate small biopsies obtained by image guided lung core or bronchoscopy over three years, from 2020-2022. Tumour morphology was evaluated, and immunohistochemistry was performed in 132 cases of lung carcinoma. In this study a small panel of three markers (TTF-1, p63 and synaptophysin) was applied as an initial approach to classify different subtypes of lung carcinoma. Additional markers (such as NapsinA, p40, CK5/6, CD56, INSM1, CK7, CK20, etc.) were incorporated based on factors like morphological characteristics, clinical information, imaging data, and the results of the initial marker panel. The largest group observed in this study comprised 67% of adenocarcinomas that showed positivity for either TTF-1 or NapsinA. Squamous cell carcinomas, identified either through p63 expression or other markers such as p40/CK5/6, accounted for 26% of cases. Additionally, 10% of cases demonstrated reactivity to neuroendocrine markers, indicating the presence of neuroendocrine tumors. Notably, immunohistochemistry successfully identified the metastatic site for 10 adenocarcinomas that were negative for both TTF-1 and NapsinA.Conclusion: A small panel of immunomarkers can classify the lung cancer reliably and increases the confidence at all level of lung cancer management.Pulse Vol.15, 2023 P: 16-21